2017
DOI: 10.1021/acs.chemmater.7b02425
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanistic Study of Phase Transformation in Perovskite Nanocrystals Driven by Ligand Passivation

Abstract: Active control over the shape, composition, and crystalline habit of nanocrystals has long been a goal. Various methods have been shown to enable postsynthesis modification of nanoparticles, including the use of the Kirkendall effect, galvanic replacement, and cation or anion exchange, all taking advantage of enhanced solid-state diffusion on the nanoscale. In all these processes, however, alteration of the nanoparticles requires introduction of new precursor materials. Here we show that for cesium lead halide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
225
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(240 citation statements)
references
References 40 publications
14
225
0
1
Order By: Relevance
“…species do not bind to the surface. [40][41][42] Surface cesium can be replaced by the oleylammonium head group in a substitution mechanism. 41 Alternatively, oleylammonium can bind surface halides through an addition mechanism.…”
Section: Scheme 1 Nanocrystal Ligand Binding Motifs According To Thementioning
confidence: 99%
“…species do not bind to the surface. [40][41][42] Surface cesium can be replaced by the oleylammonium head group in a substitution mechanism. 41 Alternatively, oleylammonium can bind surface halides through an addition mechanism.…”
Section: Scheme 1 Nanocrystal Ligand Binding Motifs According To Thementioning
confidence: 99%
“…These Cs 4 PbX 6 NCs are spherical or hexagonally shaped for small NCs (<20 nm) and often rhombohedral for larger NCs, which strongly differs from the highly cubic CsPbX 3 NCs, and strongly reflects their hexagonal crystal structure. 13,33,37 Interestingly, these NCs are often synthesized under similar conditions to those of the highly luminescent CsPbBr 3 NCs, but they use a higher amount of alkylamine. Here, the nucleation of CsPbBr 3 can be completely suppressed because oleylamine strongly binds to Pb 2+ .…”
mentioning
confidence: 99%
“…13,27 This can be done via the insertion of PbBr 2 , the extraction of CsBr with water or with Prussian Blue, or the extraction of Pb 2+ with amines. 13,27,28,33,37 Several groups have reported that the size and shape of the starting Cs 4 PbBr 6 NCs can be used to tune the size of the final CsPbBr 3 NCs (Figure 5b). 13,27,28,33,37 The transformed CsPbBr 3 NCs exhibit a strong green PL, similar to the PL of directly synthesized CsPbBr 3 NCs, and they show no excitonic absorption in the UV from their parent Cs 4 PbBr 6 NCs (Figure 5c).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This again suggest that the ligand branching, affecting surface packing and ligand diffusion in solution and through the ligand monolayer, is a critical factor. Further, as it is known that surface trap states in LHP nanocrystals, 57 and the crystal phase, 66 both strongly affect photoluminescence brightness, it seems that the changing base : acid ratio in our study is having a significant effect on surface structure, passivation and/or crystal structure, but a lesser effect on the overall size of the nanocrystals.…”
Section: Discussionmentioning
confidence: 59%